Tetrahedron-based deep-ultraviolet nonlinear optical crystal with optimized KBe2BO3F2-like structure and disordered cations. (4th April 2023) - Xu, Junxin; Sha, Hongyuan; Shang, Yanran; Wang, Zujian; Su, Rongbing; He, Chao; Yang, Xiaoming; Long, Xifa
Abstract : The Li2 NH4 Rb(SO4 )2 crystal exhibits a strong second-harmonic generation response of 2 × KH2 PO4 and a large band gap of 7.56 eV. Abstract : On account of the development of deep-ultraviolet (DUV) nonlinear optical (NLO) crystals, tetrahedron-based compounds have attracted more and more attention, due to their large band gap. Thus, it is urgent to study a lot of these crystals for conducting structural optimization to achieve a balance of optical properties. Thus, this paper designs and obtains the Li2 NH4 Rb(SO4 )2 crystal, an alkali metal sulfate, which is composed of an optimized KBe2 BO3 F2 -like structure and disordered Rb and [NH4 ] cations. It exhibits a strong second-harmonic generation (SHG) response of 2 × KH2 PO4, a large band gap of 7.56 eV and a favorable growth habit to large crystals, simultaneously. Thus, the Li2 NH4 Rb(SO4 )2 crystal is a typical tetrahedron-based DUV NLO example. The coordination of the optimized KBe2 BO3 F2 -like structure and the disordered cations results in the strong SHG response. This structural design strategy will facilitate the exploration of novel DUV NLO crystals.